I fight, therefore I am: Success factors of Roma university students from Serbia - Simic, Natasa; Vranješević, Jelena (Psihološka istraživanja, 2022)
Despite the improvements in the inclusive policies and practices, Roma students are still underrepresented in higher education (HE) in Serbia. The aim of this study was to ascertain contextual and personal factors of success of Roma HE students and to define recommendations for the improvement of HE inclusiveness. Study participants were Roma studying at four public Universities in Serbia who filled in the questionnaire on their family background and experience throughout schooling, participated in the interviews on their educational trajectories, and in a two-day workshop dedicated to empowering students through reflecting upon their educational trajectories and personal strengths. Qualitative thematic analysis of open-ended questions from 89 questionnaires, 20 interviews and the products of 16 workshop participants showed that family- and school-related challenges, such as loss of parent(s), dysfunctional family relationships and bullying served as a stimulus for personal growth in case there was at least one significant person who provided support. Scholarships and affirmative measures by enrolment were also important success factors. Students’ life mottos predominantly contained the themes of fight and persistence. Most personal strengths related to proactivity and optimism and stemmed from the support students received from significant others. This points to a highly developed psychological capital of Roma HE students. Besides continuous financial support, participants stressed that provision of continuous psychosocial support, informal learning opportunities and opportunities for peer mentorship and networking would result in more Roma students in HE.